Vascular Access And Infection Risk: Advances In Catheter-Related Bloodstream Infection Prevention (The Review of Diabetic Studies, 2024)
BackgroundCRBSIs result from microbial biofilms on catheters, primarily coagulase-negative staphylococci, S. aureus, Gram-negatives, and Candida, with ICU rates of 1.8-5.2 per 1,000 catheter-days and higher in high-risk groups like hemodialysis patients. Key risks span patient factors (immunosuppression, diabetes), device characteristics (multilumen, dwell time), and procedural issues.​MethodsNarrative synthesis of contemporary literature on prevention advances, including vascular device selection (peripheral vs. central), insertion practices (ultrasound, maximal barriers, chlorhexidine), maintenance bundles (asepsis, dressings), antimicrobial innovations (coated catheters, lock solutions), and system-level interventions (training, surveillance) in diverse settings.​ResultsEvidence-based bundles yield 40-60% CRBSI reductions; ultrasound guidance cuts risks by 30-35%; chlorhexidine dressings and antibiotic locks achieve 20-70% decreases; specialized teams lower rates below 1 per 1,000 catheter-days in optimized ICUs. Antimicrobial technologies show superior efficacy in prolonged-use scenarios.​ConclusionsIntegrated strategies across the device lifecycle dramatically mitigate CRBSIs, though challenges persist in resource-limited contexts and with multidrug-resistant pathogens; prioritize bundle adherence, novel coatings, and tailored protocols for sustained global impact.​